Implications of climate change for Ghana’s economy - Arndt, Channing; Asante, Felix A.; Thurlow, James (MDPI, 2015)
Long-run economic development in Ghana is potentially vulnerable to anthropogenic climate change given the country’s dependence on rain-fed agriculture, hydropower and unpaved rural roads. We use a computable general equilibrium model, informed by detailed sector studies, to estimate the economy-wide impacts of climate change under four climate projections. Climate change is found to always reduce national welfare, with poor and urban households and the northern Savannah zone being the worst affected. However, there is wide variation across scenarios in the size of climate impacts and in the relative importance of sectoral impact channels, thus underscoring the need for multi-sector approaches that account for climate uncertainty. Our analysis of adaptation options indicates that investing in agricultural research and extension, and improved road surfaces, are potentially cost-effective means of mitigating most of the damages from climate change in Ghana.